Penggunaan Audio Spectrum dan Genetic Algorithm Untuk Obstacle Generation Game Platforming Berbasis Musik - Octaviano, Calvin; Purba, Kristo Radion; Palit, Henry (Jurnal Infra, 2018)
Advancement in technology helps the development of hobbies such as listening to music and playing games, but in reality, both hobbies done simultaneously is rarely met, because of that, a program was developed to help in combining both hobbies into one activity with the help of Unity game engine while using widely known OGG audio file format to generate a level for a platforming game.Genetic algorithm was used as a method to deliver a process of developing level with hopes that the level structure matches the difficulty chosen by user, while also reducing the probability of a same level appearing twice, increasing game repetitiveness and minimalizing bore level.Penggunaan Audio Spectrum dan Genetic Algorithm Untuk Obstacle Generation Game Platforming Berbasis Musik